2019
DOI: 10.1177/2043808719860717
|View full text |Cite
|
Sign up to set email alerts
|

Biased attention to threat and anxiety: On taking a developmental approach

Abstract: Several researchers have proposed a causal relation between biased attention to threat and the development and maintenance of anxiety disorders in both children and adults. However, despite the widely documented correlation between attention bias to threat and anxiety, developmental research in this domain is limited. In this review, we highlight the importance of taking a developmental approach to studying attention biases to threat and anxiety. First, we discuss how recent developmental work on attention to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 172 publications
2
31
1
Order By: Relevance
“… Note: For a comprehensive review of these tasks and how they were modified from classic adult visual-attention tasks for use with infants, see Burris, Buss, LoBue, Pérez-Edgar, and Field (2019). …”
Section: Is There Room For Development In Attention Biases For Threat?mentioning
confidence: 99%
See 3 more Smart Citations
“… Note: For a comprehensive review of these tasks and how they were modified from classic adult visual-attention tasks for use with infants, see Burris, Buss, LoBue, Pérez-Edgar, and Field (2019). …”
Section: Is There Room For Development In Attention Biases For Threat?mentioning
confidence: 99%
“…In the visual paired-comparison task (d; two trials are shown), infants are presented with two images simultaneously. For a comprehensive review of these tasks and how they were modified from classic adult visual-attention tasks for use with infants, see Burris, Buss, LoBue, Pérez-Edgar, and Field (2019). Face stimuli shown here are from the NimStim Set of Facial Expressions (Tottenham et al, 2009).…”
Section: Is There Room For Development In Attention Biases For Threat?mentioning
confidence: 99%
See 2 more Smart Citations
“…Several versions of the dot probe procedure have been used to investigate attentional processes in a broad range of problems, like anxiety, depression, addiction, obesity, and problematic eating behavior (Puliafico and Kendall, 2006 ; Field et al, 2016 ; Starzomska, 2017 ; Jiang and Vartanian, 2018 ; Burris et al, 2019 ; Rojo-Bofill et al, 2019 ; Kemps et al, 2020 ), encompassing a large variety in task characteristics like presentation times, stimulus types (verbal, pictorial), stimulus alignment (vertical, horizontal), instruction (detect probe, categorize probe orientation), and number of trials. Despite this procedural variability, the basic set-up of a trial in the dot probe is rather straight-forward.…”
Section: Introductionmentioning
confidence: 99%